Fidelity of motivational interviewing in an oral health intervention with caregivers of young children - Ripplinger,Tamara (2022)
Abstract: The aim of this study was to assess the fidelity of a motivational interviewing (MI) intervention with caregivers of young children in primary healthcare in Southern Brazil. Seven trained interventionists conducted one MI session with each caregiver at their home. The sessions were audio-recorded and a randomly selected subset (n = 109) was coded by a single reviewer using the Motivational Interviewing Treatment Integrity 3.1.1. criteria (MITI 3.1.1.). This instrument establishes parameters of MI proficiency for beginners and experts measuring the global ratings of five MI principles (evocation, collaboration, autonomy/support, direction and empathy), the global MI spirit score, and the behavior counts of MI basic skills: to inform, to ask, and to listen. The mean global MI spirit rating was 4.0 (95%CI 3.9–4.1). Mean MI principle scores ranged from 3.8 (95%CI 3.7–3.9) to 4.3 (95%CI 4.2–4.4). The overall reflection-to-question ratio was 0.9 (95 CI 0.8–1.0), % open questions was 76.3 (95%CI 73.1–79.6), % complex reflections was 66.1 (95%CI 63.1–69.1), and % MI-adherent information was 94.1 (95%CI 93.5–94.5). Interventionists with higher scores conducted more and longer sessions than those with lower scores (p = 0.012). Those with beginner proficiency had a higher proportion of caregivers changing their oral health knowledge (p = 0.005). In conclusion, a good degree of MI fidelity was found, with higher fidelity among interventionists who conducted more interviews and spent more time talking with caregivers.